[PP.25.13] PRIMARY ALDOSTERONISM AND LEFT VENTRICLE IN 2D ECHOCARDIOGRAPHY: NEW INSIGHTS. (September 2016) - Boulestreau, R.; Cremer, A.; Gaillard, P.; Papaioannou, Y.; Laine, M.; Gosse, P.
Abstract : Objective: Although primary aldosteronism (PA) is the first cause of secondary hypertension and has shown a higher prevalence of cardiovascular complications, left ventricular systolic and diastolic function is not fully described. We compared with new echocardiographic tools left ventricular geometry, systolic and diastolic function between patients with PA and with essential hypertension (EH). Design and method: We extracted patients with PA from Bordeaux hypertension excellence center database, and matched them with EH patients on 24 hours blood pressure monitoring levels, age, sex, body mass index. We compared left ventricular mass (LVM), geometry, left ventricular ejection fraction (LVEF), longitudinal, circonferential and radial systolic strain, diastolic function and left atrial volume. Results: 35 patients with PA were strictly matched with 35 patients with EH for gender (sex ratio respectively 0, 54 vs 0, 54, p = 1), age (51, 1 ± 12, 2 vs 49, 3 ± 13, 8 years, p = 0, 55), 24 hours systolic and diastolic blood pressure (148, 3 ± 17, 9 vs 145, 3 ± 13, 6 mmHg, p = 0, 43 and 95 ± 10, 7 vs 94, 9 ± 11, 2 mmHg, p = 0, 95) and body mass index (27, 6 ± 3, 6 vs 27, 3 ± 5, 6 k/m 2, p = 0, 81). Indexed LVM was higher (60, 6 ± 16, 1 vs 47, 3 ± 18.6 g/m2.7, p = 0, 003), left ventricular geometry more concentric (Relative wall thickness = 0, 44 ± 0, 08 vs 0, 36 ± 0, 06, p < 0.001) and absolute longitudinal systolic strain lower (17.8 ± 3, 4 vs 20.3 ± 3, 6 %, p = 0, 004) in PA group versus EH group, respectively. We found a trend to an increased left atrial volume (65.6 ± 22, 9 ml vs 56, 1 ± 21, 3 ml, p = 0, 086). No other significant difference was found. Conclusions: This is the first study to describe left ventricular longitudinal systolic function's degradation in PA. We found as others, a LVM and maybe atrial volume higher than in EH. These 2 parameters being independent predictors of cardiovascular events, they may explain, at least partially, the higher prevalence of cardiovascular events in patients with PA.